(untitled) (TSUL LEGAL REPORT, 2026)
This research examines the complex multi-level system of civil law relations subjects operating within the biotechnology sector. The study addresses the theoretical foundations and practical aspects of biotechnology legal frameworks, analyzing the intricate relationships between primary, secondary, and regulatory actors in the biotechnology ecosystem. The research methodology encompasses comparative legal analysis, institutional economics approaches, and multi-helix innovation models to understand the distinctive characteristics of biotechnology civil law relations. The investigation reveals that biotechnology sector subjects fundamentally differ from traditional civil law classifications, requiring specialized theoretical approaches due to their interdisciplinary nature and complex multi-layered structure. Results demonstrate that successful biotechnology systems depend on balanced regulatory frameworks, multi-sectoral cooperation, and continuous adaptability principles. The research scope extends to international experiences from the United States, the European Union, and Japan, providing insights for developing nations. Key findings indicate that digital transformation creates new subject categories, including AI-powered drug discovery companies and blockchain-based solutions, fundamentally altering traditional biotechnology ecosystems. The study concludes that future biotechnology subject systems will become increasingly complex, with emerging fields like synthetic biology, convergent technologies, and quantum biotechnology requiring new legal frameworks and ethical considerations.